Literacy and the politics of writing - Gaur, Albertine (Intellect, 2000)
With the growth of modern information technology, it is time to re-examine the concept and purpose of writing, and question the long cherished idea that the alphabet stands at the apex of a hierarchy towards which all 'proper' forms of writing must necessarily progress. This beautifully illustrated book shows that the primary purpose of writing is the ability to store and transmit information, information essential to the social, economical and political survival of a particular group. Writing, in whatever form, allows the individual the interact with the group, to acquire an amount of knowled.